Find the inverse of f(x) = (3x - 6)/2

  • Google+ icon
  • LinkedIn icon
  • 695 views

First, imagine that f(x) is written as y: 

y = (3x -6)/2

swap the variables over so you write y as x and x as y:

x = (3y - 6)/2

Next, solve for x (try and get the y on its own on the right hand side)

2x = 3y - 6

2x + 6 = 3y

(2x + 6)/3 = y

Finally, swap the x and y back over to receive your answer!

f(x)' = (2x + 6)/3

where f(x)' is the inverse of f(x)

Arantxa  B. A Level Biology tutor, GCSE Maths tutor, A Level Maths tu...

About the author

is an online A Level Maths tutor with MyTutor studying at Durham University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok